Pengaruh Tingkat Pengetahuan dan Perilaku Petani dalam Pengelolaan Usaha Tani Padi dengan Sistem Tanam Jajar Legowo di Desa Lebak Mekar Kecamatan Greged Kabupaten Cirebon - Lestari, Indah; Sriyono, Sriyono (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2021)
The Purpose of the study is: 1) to know about the knowledge of the farmers in managing rice farming with jajarlegowo planting system; 2) to know about the behavior of the farmersin managing rice farming with jajarlegowo planting system; 3) to analyze the influence of the knowledge and the behavior of the farmers in managing rice farming with jajarlegowo planting system. The study was a quantitative research with a total population of all farmers who applied the jajarlegowoplantigsystem were 35 farmers. The Sampling method of the study was total sampling method. The variables of the study were the knowledge and the behavior of the farmers in managing rice farming. The Method and the tools of collecting data used in the study were observation, questionnaires, interviews, and documentation. The analysisused was descriptive analysis of the percentage and simple regression analysis. The result of the study indicated that the knowledge of the farmer was classified into high criteria with an average of 68.27%, while the behavior of farmers in managing rice farming was in good criteria with an average of 64.19%. The knowledge of farmershad a significant effect on farmer behavior in managing rice farming. Because the results of the hypothesis test, it was known that the calculated value was 2,225. Based on the calculation of the results of the determination test, the value of R square = 0.130, this showed that the influence of the independent variable on the dependent variable was 0.130. Tujuan dari penelitian ini adalah: 1) mengetahui pengetahuan petani dalam pengelolaan usaha tani padi dengan sistem tanam jajar legowo; 2) mengetahui perilaku petani dalam pengelolaan usaha tani padi dengan sistem tanam jajar legowo; 3) menganalisis pengaruh pengetahuan dan perilaku dalam pengelolaan usaha tani padi dengan sistem tanam jajar legowo. Populasi seluruh petani yang menerapkan sistem tanam jajar legowo yang berjumlah 35 petani. Variabel penelitian ini adalah pengetahuan jajar legowo dan perilaku pengelolaan usaha tani padi. Metode dan alat pengumpulan data yang digunakan adalah observasi, angket, wawancara, dan dokumentasi. Analisis yang digunakan adalah analisis deskriptif persentase dan analisis regresi sederhana. Hasil Penelitian menunjukkan bahwa Pengetahuan petani tergolong dalam kriteria tinggi dengan rata-rata 68,27%, sedangkan untuk perilaku petani pengelolaan usaha tani padi tergolong dalam kriteria baik dengan rata-rata 64,19%. pengetahuan petani berpengaruh signifikan terhadap perilaku petani dalam pengelolaan usaha tani padi. Karena hasil uji hipotesis diketahui nilai thitung sebesar 2,225. Berdasarkan perhitungan hasil uji determinasi nilai R square = 0,130, hal ini menunjukkan bahwa besarnya pengaruh yang diberikan variabel independen terhadap variabel dependen sebesar 0,130.